O que aprendem os jornalistas? uma análise das percepções de jornalistas sobre a relação entre formação acadêmica e práticas e profissionais - Porto, Alícia da Silva Cabral (2022)
This research proposes to discuss the perceptions on the contribution of education in journalism to the professional practice of journalists graduated in the metropolitan region of Porto Alegre. Our problem is to investigate the relationship between the education and the professional practice through the individual perspectives of journalists. In order to present this discussion, a historical and normative resume of the practice of the profession and of the teaching of journalism was made to afterwards, comprehend the perceptions of the journalists considering the curricular, social and historical conjuncture of their studies and relate them to their professional performance. The methodology includes bibliographic and documental research, as well as semi-structured interviews and discursive analysis of imaginaries. In this research, we bring the interview technique in a reflective context and in which subjectivity is valued. Thereon, 18 interviewees were selected, based on the period of their graduation, areas of activity and gender. The semi-structured interview method were applied to this research corpus. In the analysis, we worked with the discursive analysis of the imaginaries and used four thematic axes as categories of presentation of results, namely: Academic instruction processes; Graduation processes and their current curricula/guidelines; Professional trajectories and practices; Differences and/or similarities amongst different professionals (generation and education). Henceforth, some inferences were made, such as: there is an appreciation for the instruction in Journalism, practically unanimous among the interviewees; the gap between theory and practice is pointed out as an important challenge in education; teaching needs to be updated to keep up with changes in the profession, mainly influenced by technological advances; the labor market generally does not encourage the qualification of journalists, especially when it comes to theoretical and reflective teaching; the excessive rejuvenation of the labor market is seen negatively among interviewees from all generations.